2020
DOI: 10.3390/toxins12020087
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Toxicity of Pinnatoxin G in Mice

Abstract: Pinnatoxin G (PnTx-G) is a marine cyclic imine toxin produced by the dinoflagellate Vulcanodinium rugosum, frequently detected in edible shellfish from Ingril Lagoon (France). As other pinnatoxins, to date, no human poisonings ascribed to consumption of PnTx-G contaminated seafood have been reported, despite its potent antagonism at nicotinic acetylcholine receptors and its high and fast-acting toxicity after intraperitoneal or oral administration in mice. The hazard characterization of PnTx-G by oral exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Its high abundance in the present study is a remarkable new interesting finding given the high concentrations observed in Playitas station. Vulcanodinium rugosum, the only one species described so far from the genus, was described in 2011 from a French Mediterranean Lagoon and is responsible for producing neurotoxic pinnatoxins (PnTXs) which have been recurrently detected in the shellfish from that region [64,65]. The morphology of Vulcanodinium cells in the samples coincide with those described by Rhodes et al and Zeng et al [64,66] as motile cells, however their benthic/planktonic character should be studied.…”
Section: Diversity and Abundance Of Harmful Benthic Dinoflagellatessupporting
confidence: 63%
See 1 more Smart Citation
“…Its high abundance in the present study is a remarkable new interesting finding given the high concentrations observed in Playitas station. Vulcanodinium rugosum, the only one species described so far from the genus, was described in 2011 from a French Mediterranean Lagoon and is responsible for producing neurotoxic pinnatoxins (PnTXs) which have been recurrently detected in the shellfish from that region [64,65]. The morphology of Vulcanodinium cells in the samples coincide with those described by Rhodes et al and Zeng et al [64,66] as motile cells, however their benthic/planktonic character should be studied.…”
Section: Diversity and Abundance Of Harmful Benthic Dinoflagellatessupporting
confidence: 63%
“…This type of cysts has been called division cysts which have been described in species considered planktonic but with an intense relationship with the benthos [67,68]. No human poisonings by PnTXs are known, however because of their high toxic potential, European Food Safety Authority (EFSA) have pointed out the need for more information on the oral toxicity of these compounds for risk assessment as seafood contaminant [65]. Therefore, future taxonomic, life cycle, and toxin studies are required from the organism found in the Canary Islands.…”
Section: Diversity and Abundance Of Harmful Benthic Dinoflagellatesmentioning
confidence: 99%
“…Orally, only three studies are available and focused on PnTX E, F, G and H (Munday et al, 2012;Selwood et al, 2014; ANSES-University of Trieste-CNRS report, 2014 also published in Sosa et al, 2020). We did not find any information on the toxicity by the oral route for PtTXs (metabolites of certain PnTXs) and portimine (a toxin also produced by V. rugosum).…”
Section: Acute In Vivo Toxicity With Purified Pntxsmentioning
confidence: 87%
“…The second point relies on neurotoxic symptoms, quickly leading to the mouse's death by respiratory arrest. Clinical signs of toxicity, regardless of the route of administration and the PnTX analogue, include decreased mobility (sometimes preceded by an initial phase of hyperactivity immediately following administration), paralysis of the hind legs and breathing difficulties (Munday et al, 2012), with tremors and jumps also being reported (ANSES-University of Trieste-CNRS Report, 2014;Sosa et al, 2020). In the study by Munday et al (2012), the authors reported that at sublethal doses (without specifying which ones), some mice recovered completely after exhibiting symptoms.…”
Section: Acute In Vivo Toxicity With Purified Pntxsmentioning
confidence: 99%
“…In the present study, PnTX-G reached a maximum of 5.25 µg/kg ( M. chilensis ), much lower than the proposed level. A very recent study has allowed to stablish an oral LD 50 for PnTx-G of 208 μg/kg and a provisional No Observed Effect Level (NOEL) of 120 μg/kg [ 35 ].…”
Section: Discussionmentioning
confidence: 99%